Monocular Accounting and its Discontents: The case of the stability and growth pact - Jakob Kapeller; Leonhard Dobusch; Sabine Wandl (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2016)
This paper addresses the issue of unanticipated incentives and related unintended consequences of monocular accounting as practiced in the context of the European Union's stability and growth pact. Specifically, the Maastricht treaty establishes criteria and rules to ensure budgetary discipline by regulating public debt without taking into account corresponding public assets. In a comparative empirical study of two political reactions to the Maastricht treaty we find that the latter imposes an ambivalent incentive structure, which produces unintended consequences in cases of rule-following as well as in cases of rule-evasion. In effect, monocular accounting fosters privatization and a reduction in public engagement in the case of rule-following as well as creative accounting practices and changes of public policy goals in the case of rule-evasion.
Keywords: 330